Implementasi Jasa Umum di Kabupaten Wonogiri ( Kasus Retribusi Pengendalian Menara Telekomunikasi ) - Lestari, Nita Novia; Sundarso, Sundarso; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2015)
Retribution Policy Control Telecommunication Tower aims to control the utilization of space in the area reserved for the implementation of telecommunication towers in order to be borne in accordance with the spatial regularity and the environment and meet the aesthetics and increase regional revenue. This study was conducted to describe and analyze the factors that stimulate and inhibit, and how levies Control Policy Implementation Telecommunication Tower in Wonogiri. The research method used is to observe the accuracy policy, the accuracy of the implementation, the target accuracy, precision environmental and policy implementation model of George C. Edwards III. The process of policy implementation Levy Control Telecommunication Tower At Department of Communication and Information in Wonogiri practice there are inhibiting factors and supporting its implementation. The author recommends: (1) co-coordinating and awareness tower providers in terms of transfer of ownership of the tower immediately communicated to the Department so that appropriate billing and payment processes and fast, (2) Provide sanctions on providers that tower over the time of payment.